Case Series Using a Novel Implant and Accelerated Rehabilitation for Patients Undergoing an Isolated Talonavicular Arthrodesis. Issue 3 (June 2016) - Shymon, Stephen Joseph; Moss, Lewis; Harris, Thomas Gregory
Talonavicular (TN) arthrodeses for TN arthritis have a high rate of nonunions for an essential hindfoot joint. In this case series, 12 patients underwent an isolated TN arthrodesis using a novel implant (IO FiX) by a single surgeon with a minimum 1-year follow-up (30.1 ± 14.7 months; mean ± SD). All patients (62 ± 12 years) underwent an aggressive rehabilitation protocol given the strength and compression of the implant. There were no nonunions, nor were there any patients lost to follow-up. Time to radiographic union was 9.6 ± 1.4 weeks. The Visual Analog Scale pain level decreased from 7.3 ± 0.9 preoperatively to 2.1 ± 0.7 postoperatively (P < .001). The Short-Form-12 physical component improved from 27.9 ± 4.2 preoperatively to 42.2 ± 3.5 postoperatively (P < 0.001), while the Short-Form-12 mental component did not change from 50.8 ± 6.9 preoperatively to 54.4 ± 3.8 postoperatively (P > .05). Use of the novel fixation device for TN arthrodesis by a single surgeon with an accelerated rehabilitation protocol significantly decreased patients' pain and improved their physical functional outcomes (P < .001). The IO FiX implant can potentially improve TN arthrodesis fusion rates and surgical outcomes. Levels of Evidence: Therapeutic, Level IV: Case series